Study on the Parameter Optimization and Strength Mechanism of Coal Gangue Emulsified Asphalt Mixture - ZhanLiang Liu; Chen Zhang; Xin Qu (Advances in Materials Science and Engineering)
Emulsified asphalt mixture has the characteristics of convenient construction and durable performance, but its poor early strength and demulsification seriously restrict the popularization and application of this material. At present, the coal gangue produced by coal-fired power plants is generally discarded, resulting in serious environmental pollution. The combination of coal gangue and emulsified asphalt can explore an efficient utilization way for more and more coal gangue and also solve the curing problem of asphalt. In order to give full play to the advantages of existing materials and make rational use of resources, this paper studies the factors affecting the performance of coal gangue emulsified asphalt mixture based on orthogonal experimental design and optimizes its material composition parameters by considering the coupling effect of two factors. The water stability of coal gangue emulsified asphalt mixture is evaluated by the immersion Marshall test. Finally, the strength formation mechanism of coal gangue emulsified asphalt mixture is analyzed from the microscopic point of view. The results determined 7.5% as the optimum amount of emulsified asphalt in coal gangue emulsified asphalt mixture and recommended the best parameter combination of 7.5% emulsified asphalt, 6% coal gangue, and 5% water consumption. With the increase of coal gangue content, the water loss resistance of emulsified asphalt mixture increases gradually, and the water stability of emulsified asphalt mixture can be improved by adding coal gangue. According to the microscopic analysis, the strength of the mixture is formed by the joint action of emulsified asphalt and coal gangue, in which the hydration products of coal gangue and asphalt play the role of cementation and strength together. The ordinary emulsified asphalt mortar mainly contains CaCO3, which mainly plays the role of physical filling.